Role of p53 in different colorectal carcinogenesis pathways Is it relevant for clinical practice? - Sacramento, Maria Luísa Noites (2020)
p53 is a protein that regulates cell cycle, apoptosis and genomic stability. It is thought to be responsible for the progression from dysplasia to colorectal cancer (CRC), in sporadic cancers. In Inflammatory Bowel Disease (IBD) patients, CRC can occur as a result of the chronic inflammatory state or it may simply be sporadic, evolving from adenomas (precursor lesions). In these two distinct pathways, p53 mutations occur in different stages. In patients with colitis-associated cancer (CAC), p53 mutation is usually an early event. In contrast, in sporadic carcinogenesis, p53 mutation will only occur later in the process. A project will be proposed regarding the analysis of lesions from a cohort of patients with IBD and any form of dysplasia/CRC diagnosis followed at Instituto Português de Oncologia de Lisboa Francisco Gentil (IPOLFG). Immunohistochemistry will be used to assess p53 protein expression – lesions endoscopically classified as adenomalike (controls) will be compared to non-adenoma-like lesions (cases). By using p53 immunoexpression analysis, it may be possible to distinguish between sporadic CRC and CAC in the context of IBD. These have different implications regarding therapeutic decisions and patient prognosis.